2009
DOI: 10.1016/j.jcrs.2008.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound biomicroscopic evaluation of the efficacy of a transillumination technique for ciliary sulcus localization in transscleral fixation of posterior chamber intraocular lenses

Abstract: Ultrasound biomicroscopy showed the difficulty in reliably suturing the haptics in the ciliary sulcus, even with the use of a transillumination technique. However, the results suggest that the transillumination technique is a safe and easy procedure and helps the surgeon identify the ciliary sulcus during transscleral fixation of PC IOLs more precisely than without the use of transillumination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…[31] In another UBM study of haptics in trans sclera fixated IOL, it was reported that correctly placed haptics was present in 33% cases; where as 50% were located posterior to the sulcus and 17% were placed anterior to the sulcus. [32] Various methods for ciliary sulcus localization have been used and are reported in literature eg., transillumination with endo-illuminator [31] and mirror needle holder. [33] With transillumination technique of localization of ciliary sulcus, haptic placement in sulcus improved to 64%.…”
Section: Discussionmentioning
confidence: 99%
“…[31] In another UBM study of haptics in trans sclera fixated IOL, it was reported that correctly placed haptics was present in 33% cases; where as 50% were located posterior to the sulcus and 17% were placed anterior to the sulcus. [32] Various methods for ciliary sulcus localization have been used and are reported in literature eg., transillumination with endo-illuminator [31] and mirror needle holder. [33] With transillumination technique of localization of ciliary sulcus, haptic placement in sulcus improved to 64%.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound biomicroscopy, a technique that allows for a real time panoramic view to image the anterior segment, revealing the ciliary body and peripheral retina, was found as an adjuvant tool to evaluate the placement of the IOL postoperatively [19, 20]. …”
Section: Discussionmentioning
confidence: 99%
“…In another study by Alp et al, UBM examination showed that the rate of haptics located in the sulcus was statistically significantly higher in the endoilluminator-assisted group (64%) than in the control group (24%) ( p = 0.001), which reflects the limitations of the blind needle penetration method for precise suturing in the ciliary sulcus [19]. …”
Section: Discussionmentioning
confidence: 99%
“…In adults, there is evidence that the dark scleral band in the perilimbal region demonstrated by scleral transillumination (STI) is a reliable and quick method to identify ciliary body when compared to in‐vivo ultrasound biomicroscopy (UBM) imaging . Patel et al demonstrated the use of STI in premature infants to identify the dark band.…”
Section: Introductionmentioning
confidence: 99%
“…11 In adults, there is evidence that the dark scleral band in the perilimbal region demonstrated by scleral transillumination (STI) is a reliable and quick method to identify ciliary body when compared to in-vivo ultrasound biomicroscopy (UBM) imaging. 12 Patel et al 13 demonstrated the use of STI in premature infants to identify the dark band. In adults, STI reveals two dark bands separating a light band with the anterior dark band corresponding with the pars plicata and light posterior band to the pars plana, whereas in infants a single dark band is apparent.…”
Section: Introductionmentioning
confidence: 99%